The Relationship Between Family Support and Health Service Utilization Among Older Adults at the Rosela Elderly Posyandu - Amir Amir; Supirno Supirno; Alfrida Samuel Ra’bung; Baiq Emy Nurmalisa; Bileam Dwiono Basolung (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
The elderly population in Indonesia is increasing, including in Central Sulawesi Province. Regular visits to the posyandu (integrated health post) are crucial for monitoring elderly health. However, participation at the Rosela Posyandu remains suboptimal, and family support has been identified as a potential contributing factor. Nevertheless, empirical evidence on this relationship in this specific setting is limited. This study aimed to analyze the relationship between family support and elderly visits to the Rosela Posyandu in the working area of the Mamboro Community Health Center, Palu Utara District. This study employed a quantitative cross-sectional design. The population consisted of all registered older adults (aged 45 years and over) at the Rosela Posyandu, totaling 30 respondents, who were recruited using total sampling. Data were collected using a validated questionnaire to measure family support and posyandu attendance records to assess visit frequency, categorized as active (≥3 visits in the last 3 months) or inactive (<3 visits). Data analysis was performed using the Chi-square test with a significance level of p < 0.05. The majority of respondents were aged 45–59 years (57%), female (87%), and had elementary school education (30%). Among 30 respondents, 24 (80%) received supportive family support, while 6 (20%) did not. Of those with family support, 19 (79.2%) were active visitors, whereas all respondents without family support (100%) were inactive. The Chi-square test revealed a significant relationship between family support and elderly visits (p = 0.002). This study confirms a significant association between family support and elderly visits to the Rosela Posyandu. These findings highlight the need for family-centered health promotion strategies to improve elderly participation. Future research with larger samples and longitudinal designs is recommended.